The response of porcine monocyte derived macrophages and dendritic cells to Salmonella Typhimurium and lipopolysaccharide - Kyrova, Kamila; Stepanova, Hana; Rychlik, Ivan; Polansky, Ondrej; Leva, Lenka; Sekelova, Zuzana; Faldyna, Martin; Volf, Jiri (BMC veterinary research, 2014)
BACKGROUND: Following infection and initial multiplication in the gut lumen, Salmonella Typhimurium crosses the intestinal epithelial barrier and comes into contact with cells of the host immune system. Mononuclear phagocytes which comprise macrophages and dendritic cells (DC) are of key importance for the outcome of Salmonella infection. Although macrophages and DC may differentiate from a common precursor, their capacities to process and present antigen differ significantly. In this study, we therefore compared the response of porcine macrophages and DC differentiated from peripheral blood monocytes to S. Typhimurium and one of the most potent bacterial pathogen associated molecular patterns, bacterial lipopolysaccharide. To avoid any bias, the expression was determined by protein LC-MS/MS and verified at the level of transcription by quantitative RT-PCR. RESULTS: Within 4 days of culture, peripheral blood monocytes differentiated into two populations with distinct morphology and expression of MHC II. Mass spectrometry identified 446 proteins in macrophages and 672 in DC. Out of these, 433 proteins were inducible in macrophages either after infection with S. Typhimurium or LPS exposure and 144 proteins were inducible in DC. The expression of the 46 most inducible proteins was verified at the level of transcription and the differential expression was confirmed in 22 of them. Out of these, 16 genes were induced in both cell types, 3 genes (VCAM1, HMOX1 and Serglycin) were significantly induced in macrophages only and OLDLR1 and CDC42 were induced exclusively in DC. Thirteen out of 22 up-regulated genes contained the NF-kappaB binding site in their promoters and could be considered as either part of the NF-kappaB feedback loop (IkappaBalpha and ISG15) or as NF-kappaB targets (IL1beta, IL1alpha, AMCF2, IL8, SOD2, CD14, CD48, OPN, OLDLR1, HMOX1 and VCAM1). CONCLUSIONS: The difference in the response of monocyte derived macrophages and DC was quantitative rather than qualitative. Despite the similarity of the responses, compared to DC, the macrophages responded in a more pro-inflammatory fashion.
Keywords: buněčná diferenciace; Swine; Lipopolysaccharides; makrofágy; Salmonella typhimurium; Cells, Cultured; Dendritic Cells; Animals; prasata; Macrophages; Gene Expression Regulation; zvířata; lipopolysacharidy; kultivované buňky; regulace genové exprese; Cell Differentiation; dendritické buňky